2018
DOI: 10.1137/17m1124796
|View full text |Cite
|
Sign up to set email alerts
|

Density-Equalizing Maps for Simply Connected Open Surfaces

Abstract: In this paper, we are concerned with the problem of creating flattening maps of simplyconnected open surfaces in R 3 . Using a natural principle of density diffusion in physics, we propose an effective algorithm for computing density-equalizing flattening maps with any prescribed density distribution. By varying the initial density distribution, a large variety of mappings with different properties can be achieved. For instance, area-preserving parameterizations of simply-connected open surfaces can be easily … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Figs. 5ce show the results generated at the non-convex corner of the L-shaped domain by the density-equalizing map (DEM) [28], the shape-prescribed density-equalizing map (SPDEM) [27] and the proposed DERM method. For both DEM and SPDEM, the density was set to be the face area for computing area-preserving flattening maps.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figs. 5ce show the results generated at the non-convex corner of the L-shaped domain by the density-equalizing map (DEM) [28], the shape-prescribed density-equalizing map (SPDEM) [27] and the proposed DERM method. For both DEM and SPDEM, the density was set to be the face area for computing area-preserving flattening maps.…”
Section: Resultsmentioning
confidence: 99%
“…We consider zooming into the non-convex corner of the L-shaped domain as illustrated in a. In b, c, d, e, the mapping results at that region produced by the ALS mapping method [23], the density-equalizing map (DEM) [28], the shape-prescribed density-equalizing map (SPDEM) [27] and the proposed DERM method are respectively shown. It can be observed that our method is advantageous in adjusting for the geometric variability of the carotid surfaces without causing any overlaps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To simplify the mapping problem, we begin with flattening S i and S j onto the plane. While there exists other flattening methods such as area-preserving maps [27,28], conformal parameterizations are preferred in our case as they preserve the Beltrami coefficient and hence the conformal distortion under compositions. Following the approach in [21], we compute two conformal maps g i : S i → R i and g j : S j → R j that flatten S i and S j onto two rectangular domains R i , R j on the plane.…”
Section: Rectangular Conformal Parameterizationsmentioning
confidence: 99%